2018
DOI: 10.1007/s00775-018-1539-7
|View full text |Cite
|
Sign up to set email alerts
|

Emission of volatile halogenated compounds, speciation and localization of bromine and iodine in the brown algal genome model Ectocarpus siliculosus

Abstract: This study explores key features of bromine and iodine metabolism in the filamentous brown alga and genomics model Ectocarpus siliculosus. Both elements are accumulated in Ectocarpus, albeit at much lower concentration factors (2-3 orders of magnitude for iodine, and < 1 order of magnitude for bromine) than e.g. in the kelp Laminaria digitata. Iodide competitively reduces the accumulation of bromide. Both iodide and bromide are accumulated in the cell wall (apoplast) of Ectocarpus, with minor amounts of bromin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 54 publications
1
17
1
Order By: Relevance
“…Very little is known about the regulation and homoeostasis of halogen accumulation in seaweeds in general. Ar Gall et al (2004) found iodine levels in the kelp L. digitata to be around half of their winter levels during summer, while a competitive inhibition of bromide accumulation by increased, exogenous iodide levels (which may be somewhat reminiscent of the results of the present study) was observed in the filamentous brown alga Ectocarpus (Küpper et al 2018). However, given the very different physico-chemical properties of iodide and fluoride, it seems unlikely that the same transport and storage mechanisms are operative for both.…”
Section: Discussionsupporting
confidence: 70%
“…Very little is known about the regulation and homoeostasis of halogen accumulation in seaweeds in general. Ar Gall et al (2004) found iodine levels in the kelp L. digitata to be around half of their winter levels during summer, while a competitive inhibition of bromide accumulation by increased, exogenous iodide levels (which may be somewhat reminiscent of the results of the present study) was observed in the filamentous brown alga Ectocarpus (Küpper et al 2018). However, given the very different physico-chemical properties of iodide and fluoride, it seems unlikely that the same transport and storage mechanisms are operative for both.…”
Section: Discussionsupporting
confidence: 70%
“…Using the macroalga Ectocarpus, which can be grown reproducibly in the laboratory and has a halogen metabolism that has been recently studied (Küpper et al 2018), we have also investigated the possibility that iodate as well as iodide can be taken up by brown macroalgae. We found that over a time period of days to weeks, iodate concentrations in media containing growing Ectocarpus cultures were found to fall significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of S-adenosyl-methionine-dependent methyl transferase-type mechanism has also been reported in relation to the production of methyl halides (Almeida et al 2001;Toda and Itoh, 2011;Yokouchi et al 2014). The activities of methyl transferases yield monohalogenated compounds including CH3Br, CH3I, di-and polyhalogenated compounds such as CHBr2I (Milkova et al 1997;Neilson, 2003;Amachi et al 2006;Küpper et al 2018). Punitha et al (2017) gives a detailed explanation of the reactions.…”
Section: Introductionmentioning
confidence: 93%